Desenvolvimento de sistemas biométicos para detecção de bumetanida e hidroclorotiazida em amostras de interesse farmacêutico e biológico - Ruy, Mayara Regina dos Santos [UNESP] (2015)
This work is based on the construction of biomimetic sensors for sensitive and selective determination of diuretics for bumetanide (BMT) and hydrochlorothiazide (HCTZ). Carbon paste-based electrodes were modified with complexes, which are potential biomimetic catalysts of P450 enzymes, that catalyze a number of reactions including pharmaceuticals. The complexes Copper (II) 1,2,3,4,8,9,10, 11,15,16,17,18,22,23,24,25-hexadecafluoro-29-H,31-H-phthalocyanine [CuPc] and Hemin showed biomimetic profile and better results for amperometric and voltammetric determination of bumetanide and hidroclorotiziada, respectively. The experimental conditions for the proposed methodologies development have been optimized with the help of design of multivariate experiments. The sensor built to determine the diuretic bumetanide presented the best responses in Britton-Robinson buffer 0.15 mol L-1 pH 7.0 and 15 % (m/m) of the complex [CuPc], using the square wave voltammetry with 60 Hz, amplitude of potential of 100 mV and step potencial of 6 mV. With the optimized parameters the sensor showed limits of detection and quantification of 0.27 and 0.9 μmol L-1,respectively. The best results for the sensor have been developed for hydrochlorothiazide phosphate solution 0.10 mol L-1 pH 8.5 and 14 % (m/m) of the hemin, using the amperometry at 800 mV, limits of detection and quantification of 8.2 and 27 μmol L-1, respectively. Studies conducted for elucidation of sensor biomimetic behavior, such as evaluation of scan rate influence using cyclic voltammetry, exploration of hyperbolic profile of the sensor response, interference and selectivity studies. In a complementary, a molecular imprinting polymer, known as MIP, was developed for bumetanide. The MIPs were synthesized by bulk polymerization. Studies were based on the results obtained from the computer simulation where monomer of high structural affinity, acrylonitrile...